Supply chain development drivers in industry 4.0 in Ukrainian enterprises - Yevhen Krykavskyy; Olena Pokhylchenko; Nataliya Hayvanovych (Oeconomia Copernicana, 2019)
Research background: Industry 4.0 is a response to rapid technical progress, caused by the dominant role of information technology, which covers and penetrates virtually into all the aspects of people's economic and social activities. At present, the terms “Digital Supply Chain”, “Supply Chain 4.0”, “Digital logistics”, and “Smart logistics” are widely used in business, and in particular, in the theory and practice of supply chain management (SCM). This demonstrates the relevance of the implementation of Industry 4.0 innovations into the practical activities of manufacturing, trading, and logistics companies, interconnected by networking in the process of delivering products or services to final consumers. In turn, this causes fundamental changes in the structure of supply chains, their business processes and behaviours, making existing approaches to management obsolete.